Interactive Visualization of Data on the Impact of Violent Games on the Behavior of Children and Adolescents: Action Research - Mina Jozi; Kosar Mahmoudiasl; Yoones A. Sekhavat (Vesnu Publications, 2020)
Introduction: The purpose of the present study is to graphically and comprehensively illustrate the data on the impact of violent video games on the behavior of children and adolescents. Materials and Methods: This visualization system was designed based on the Schneider principle using the results of a clinical study carried out by psychologists at the Ohio University, Athens, Ohio, United States that included 242 children aged 8 to 12 years in three groups. All groups played different versions of the Minecraft game, then using data recorded in an Excel file on the Figshare site, four variables were depicted. The variables including finding the gun, length of time the gun was held, the number of trigger pulls, as well as demographic or control characteristics of age and gender of the children were evaluated. Results: Visualization was designed in the Processing software environment and it was easy to compare the three groups using the color, shape, and coordinate channels. Accordingly, it appeared that violent behaviors in children who experienced gun play were greater than those played the sword; both of them showed more violent behaviors compared to the group who played the non-violent version. Violent behaviors were also more prevalent in male children in all three groups. In other words, girls in the 8-12 age group in all three groups were less likely to exhibit post-game aggression. Conclusion: In this study, data on the impact of violent video games on the behavior of children and adolescents were graphically and comprehensibly visualized based on the Schneider Principle and revealed that violent behaviors in children who experienced violent video games were higher than those in the control group. Violent behaviors were also more prevalent in male children in all three groups.